Perbankan Syariah Menurut H.R. Tirmidzi No. 1232 dan Pasal 4 Ayat (1) UU No. 21 Tahun 2008 - Haura Muthmainnah; Tajul Arifin (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
This study examines the relationship between the hadith of H.R. Tirmidzi No. 1232 concerning the prohibition of selling goods that are not yet owned with Article 4 Paragraph (1) of Law No. 21/2008 concerning the intermediary function of Islamic banking in Indonesia. With a descriptive-analytical approach with a juridical-normative method, this study reveals significant gaps in the implementation of regulations. While the hadith provides theological guidelines that require actual ownership before the contract, the fragmented regulatory framework results in inconsistent interpretations by the Sharia Supervisory Board in various institutions. Analysis of SINTA indexed journals shows that many Islamic banking products still contain elements of gharar (uncertainty), especially in murabahah contracts with installment payments. This study identifies three main issues: the limited explicit regulation in the DSN-MUI fatwa regarding hybrid contracts, structural challenges in Indonesia's decentralized regulatory approach compared to Malaysia's centralized model, and the gap between theoretical discourse and practical implementation. To strengthen the synergy between religious principles and regulatory mandates, this study recommends harmonization of the regulatory framework, implementation of intensive training for supervisory boards on the contextual background of related hadiths, and development of integrated compliance audits to assess product consistency with hadith guidance and legal requirements.